Ethnophysics: Reconstruction Indigenous Knowledge into Scientific Knowledge in The Brick Making Proces - Fibrika Rahmat Basuki; Jufrida Jufrida; Wawan Kurniawan; Irma Fadilah (Pendidikan Kimia Unimus, 2023)
Ethnophysics is a branch of ethnoscience that studies indigenous knowledge to be reconstructed into physical concepts. Indigenous knowledge about the brick-making process was obtained based on experience passed down from generation to generation. This study aims to reconstruct the indigenous knowledge about the brick-making process into scientific knowledge (physics). This study was a descriptive qualitative using an ethnography approach. The subject of this research was three brick craftsmen. The research was conducted in Setiti Village, Muaro Jambi Regency. Observations were carried out to collect data about tools and materials as well as the stages of the brick-making process. Interviews were conducted with brick craftsmen to collect data about the indigenous knowledge of the brick-making process. Indigenous knowledge about making-brick process was analyzed and reconstructed into scientific concepts. The brick-making process consisted of mixing clay, molding, drying in the sun, and burning at high temperatures. The identified physics concepts were a simple machine, pressure, soil, measurement, circular motion, work and energy, temperature, and heat. Indigenous knowledge about making-brick process can be integrated into physics learning at school.